TINGKAT SUHU YANG BERBEDA TERHADAP LAMA WAKTU TETAS TELUR IKAN PATIN (Pangasius hypophthalmus) DALAM AQUARIUM - Mukhlisah (Fakultas Pertanian UVAYA Banjarmasin, 2022)
The aim of this study was to determine the effect of different incubation temperature on hatching time Pangasius hypophthalmus Eggs. A completly randomized design is used this study with 3 different treatments and 3 replication. The treatments were A (27˚C), B (29˚C) and C (31˚C). The result of this study for each treatment A, B, and C indicated that average of hatching time were A 19.99 hours, B 19.08 hours and C 18.22 hours. Statistical analysis indicated that were significant differences among treatment